2011
DOI: 10.1021/jm1013715
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Biocompatible Nanoparticles for the Delivery of (−)-Epigallocatechin 3-Gallate to Prostate Cancer Cells

Abstract: Molecular targeted cancer therapy mediated by nanoparticles (NPs) is a promising strategy to overcome the lack of specificity of conventional chemotherapeutic agents. In this context, the prostate-specific membrane antigen (PSMA) has demonstrated a powerful potential for the management of prostate cancer (PCa). Cancer chemoprevention by phytochemicals is emerging as a suitable approach for the treatment of early carcinogenic processes. Since (-)-epigallocatechin 3-gallate (EGCG) has shown potent chemopreventiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
129
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(132 citation statements)
references
References 51 publications
3
129
0
Order By: Relevance
“…These polyphenols, with different chemical structures, have been selected because they have received a great deal of interest worldwide as potent bioactive substances endowed with chemopreventive/therapeutic activities because of their anti-invasive and antiproliferative effects in a wide variety of tumor cells, [23][24][25][26] with an increased effectiveness when formulated into a variety of nanosystems. [27][28][29][30][31] On the other hand, the functionalization of GNPs' surface with these bioactive substances might provide a new useful approach as delivery and therapeutic tools, in particular by improving the biopharmaceutical properties of these polyphenols, such as their poor bioavailability and stability, as well as their resistance to specific/nonspecific metabolic processes.…”
Section: Introductionmentioning
confidence: 99%
“…These polyphenols, with different chemical structures, have been selected because they have received a great deal of interest worldwide as potent bioactive substances endowed with chemopreventive/therapeutic activities because of their anti-invasive and antiproliferative effects in a wide variety of tumor cells, [23][24][25][26] with an increased effectiveness when formulated into a variety of nanosystems. [27][28][29][30][31] On the other hand, the functionalization of GNPs' surface with these bioactive substances might provide a new useful approach as delivery and therapeutic tools, in particular by improving the biopharmaceutical properties of these polyphenols, such as their poor bioavailability and stability, as well as their resistance to specific/nonspecific metabolic processes.…”
Section: Introductionmentioning
confidence: 99%
“…Polymeric EGCG-encapsulated NPs, functionalised with a mimetic ligand of the prostate specific membrane antigen (PSMA), show an improved selective EGCG delivery in PSMA expressing PCa cells thus leading to a more marked inhibition of cell proliferation [159,160]. The same Authors observed a significant increase of tumor growth inhibition in mouse xenografts treated with PSMA targeted NPs, in comparison to EGCG.…”
Section: Nanotechnology Strategies To Improve Gtcs Bioactivitymentioning
confidence: 88%
“…Epigallocatechin 3-gallate (EGCG) is a green tea catechin, which has protective effects against some common types of cancer (Yang et al, 2009). Since it was shown to be chemopreventive against prostate cancer (Bettuzzi et al, 2006;Brausi et al, 2008), an EGCG loaded nanoparticle consisting of PLGA-PEG copolymers was functionalized with an ureabased PSMA inhibitor (Sanna et al, 2011), which is capable of targeting PSMA with a similar affinity and specificity like antibodies and aptamers (Sanna et al, 2011). In in vitro experiments LNCaP cells were incubated for 1 or 3 h with the anti-PSMA nanoparticles.…”
Section: Nanoparticles Targeting Psmamentioning
confidence: 99%
“…In in vitro experiments LNCaP cells were incubated for 1 or 3 h with the anti-PSMA nanoparticles. In this assay, a significant antiproliferative effect of the nanoparticles to the tumor cells, marked by a growth inhibition up to 60% after 72 h, could be measured (Sanna et al, 2011).…”
Section: Nanoparticles Targeting Psmamentioning
confidence: 99%